(untitled) (European Journal of Pure and Applied Mathematics, 2023)
In this paper, we study the relationships between graphs and the prime spectrum of unitary commutative rings. It is shown that a graph G equipped with the G-right topology satisfies some spectral properties. In particular we give a necessarily and sufficient condition to obtain a spectral graph.